DEVELOPING STUDENTS’ SPEAKING SKILL OF GRADE XI AT SMAN 2 TOLITOLI BY USING DESCRIBING PICTURE - Inda Indrawati (Universitas Madako Tolitoli, 2018)
This study is about the use of describing picture as method to develope students’ speaking skill of the eleventh grade students of SMA Negeri 2 Tolitoli in the 2016/2017 academic year. The design of this research is pre experimental research. The sample of this research is the eleventh grade students that consist of 31 students. The data obtained from pre test and post test. In the pre test it is found that mean score of the student are 34,19 and in the post test are 69,67. Computation of the data tcount results is 19,86 which means higher than ttable is 2,042. The result indicates that there is an improvement in students’ speaking ability by using describing picture. It can be concluded that improving speaking skill by using picture is effective.Key word : Developing, Speaking Skill, Describing Picture